Real time digital control system for a single-phase shunt active power filter - Silva, Vítor (2012)
In this paper a real-time control system, developed to control a single-phase shunt active power filter used to minimize problems related to power quality in electrical systems is presented. The power stage of the active filter is based on a one-leg inverter, with two capacitors in the dc side, and a filter inductor in the ac side. The control system is based on the instantaneous power theory in the α-β-0 reference frame (pq-theory), modified to be applied in single-phase systems. In essence, the shunt active filter is designed to drain, from the electric grid, harmonic and reactive components of the load currents, such that the source current will become an almost sinusoidal waveform, with low harmonic distortion, and in phase with the system voltage. The control system is implemented using a development board (Atmel NGW100) and ensures simultaneous real-time acquisition of voltage and current data, the proposed system is capable of acquiring eight analog channels (16-bit resolution) simultaneously at 150ksps, based in the acquire data the power components calculation and compensation is performed accordingly to the p-q theory.